Studi Literatur Peranan Literasi Akuntansi dalam Pengembangan Keterampilan Bahasa dan Komunikasi Mahasiswa Akuntansi: Penelitian - Kafka Nafisa; Tamaro Maruli Simanjuntak; Natasya Perangin Angin; Rani Yunita Sari Sagala; Pandeawan Yohanes Selamat Marbun; Muhammad Anggie Januarsyah Daulay (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the role of accounting literacy in developing language and communication skills among accounting students. The research employed a literature review method by analyzing 30 nationally accredited SINTA articles published between 2016 and 2025. Data were analyzed systematically through coding, thematic analysis, and descriptive synthesis to identify research patterns and gaps. The findings indicate that accounting literacy plays a strategic role not only in enhancing technical conceptual understanding but also in strengthening students’ academic language and professional communication skills. Accounting literacy was found to support students in writing academic reports, delivering presentations, and communicating confidently in both academic and professional discussions. Furthermore, integrating accounting literacy through case-based learning, digital simulations, and literacy-based media effectively bridges conceptual understanding with communication skills. However, challenges remain, including limited comprehension of accounting terminology, reliance on traditional teaching methods, and inadequate digital infrastructure. Therefore, accounting literacy is considered a key competence that should be integrated into the accounting curriculum to support the development of students’ communication skills in both academic and professional contexts.